Shark attack! - Dubowski, Cathy East. (New York : DK Pub., 1998)
Describes the nearly disastrous encounter of a spear-fisherman with a shark off the coast of Australia.
"Grades 2 and 3."
Keywords: Shark attacks -- Juvenile literature; Shark attacks